Enhancing the get healthy information and coaching service for Aboriginal adults: evaluation of the process and impact of the program - E. Quinn; B. J. O'Hara; N. Ahmed; S. Winch; B. McGill; D. Banovic; M. Maxwell; C. Rissel (BMC, 2017)
Abstract Background Non-communicable chronic diseases in Australia contribute to approximately 85% of the total burden of disease; this proportion is greater for Aboriginal communities. The Get Healthy Service (GHS) is effective at reducing lifestyle-based chronic disease risk factors among adults and was enhanced to facilitate accessibility and ensure Aboriginal cultural appropriateness. The purpose of this study is to detail how formative research with Aboriginal communities was applied to guide the development and refinement of the GHS and referral pathways; and to assess the reach and impact of the GHS (and the Aboriginal specific program) on the lifestyle risk factors of Aboriginal participants. Methods Formative research included interviews with Aboriginal participants, leaders and community members, healthcare professionals and service providers to examine acceptability of the GHS; and contributed to the redesign of the GHS Aboriginal program. A quantitative analysis employing a pre-post evaluation design examined anthropometric measures, physical activity and fruit and vegetable consumption of Aboriginal participants using descriptive and chi square analyses, t-tests and Wilcoxon signed-rank tests. Results Whilst feedback from the formative research was positive, Aboriginal people identified areas for service enhancement, including improving program content, delivery and service promotion as well as ensuring culturally appropriate referral pathways. Once these changes were implemented, the proportion of Aboriginal participants increased significantly (3.2 to 6.4%). There were significant improvements across a number of risk factors assessed after six months (average weight loss: 3.3 kg and waist circumference reduction: 6.2 cm) for Aboriginal participants completing the program. Conclusions Working in partnership with Aboriginal people, Elders, communities and peak bodies to enhance the GHS for Aboriginal people resulted in an enhanced culturally acceptable and tailored program which significantly reduced chronic disease risk factors for Aboriginal participants. Mainstream telephone based services can be modified and enhanced to meet the needs of Aboriginal communities through a process of consultation, community engagement, partnership and governance.